Male Takeovers Are Reproductively Costly to Females in Hamadryas Baboons: A Test of the Sexual Coercion Hypothesis - Polo, Pablo; Hernández-Lloreda, Victoria; Colmenares, Fernando (PLOS ONE, 2014)
During male takeovers, in addition to fighting off the female’s current mating partner, males may exhibit intense aggressive mate guarding of the newly acquired females. Recent studies indicate that coercive sexual aggression by males is an important strategy through which sexual conflict is expressed. Previous tests of the sexual coercion hypothesis in primates have focused on assessing if female mate choice is effectively reduced by male aggression, however, only one recent study has tested a critical prediction of this hypothesis, namely, that male coercion is reproductively costly to victim females. The present study uses 15 years of data on inter-birth intervals from a large multilevel colony of baboons, mostly Papio h. hamadryas, with a mating system based on harem-defence polygyny to examine if male takeovers impact the length of the abducted females’ inter-birth intervals. Our analysis of 121 inter-birth intervals from 45 adult females indicates that male takeovers are reproductively costly to abducted females as they are associated with an increase in the time they take to conceive and a lengthening of the inter-birth intervals. We discuss how several factors may contribute to this reproductive cost, including male-female sexual conflict, male-male competition, and female-female competition. Our findings suggest that the male’s aggressive herding is the main contributor to the abducted females’ immediate reproductive cost. We argue that although some of the male’s aggressive herding may be driven by male-male competition, nonetheless, it serves a coercive function as it both constrains the female’s mate choice options and hampers her immediate breeding performance. This conclusion is backed up by results obtained in the only other study that has tested the same prediction and which has been carried out in a wild population of hamadryas baboons.